Shape Measurement Method by Integrating Stereo Vision and Shape-from-Shading with Evolutionary Programming - FUKUDA, Toshio; SHIMOJIMA, Koji; TAKUSAGAWA, Teruhiko; KOBAYASHI, Futoshi (Transactions of the Japan Society of Mechanical Engineers Series C, 1998)
In this paper, we propose a new method for measuring the shape of objects. The proposed method is based on integrating stereo vision and Shape-from Shading with Evolutionary Programming (EP). In some traditional methods the reflection of objects is diffuse reflection. But because the reflection of real objects consists of diffuse and specular reflection, some methods cannot be applied to real objects. Photometric stereo can be applied to real objects but this method needs many original image for measuring the shape accurately. The proposed method can apply Phong model to a reflectivity function and measure the shape of the object which have the effect of diffuse and specular reflection. Then, this method uses EP for identifying the reflectivity function accurately.